Parkraumbewirtschaftung - Was macht Japan anders? Bewirtschaftungsinstrumentarien im deutsch-japanischen Vergleich. - Nakamura, Hideki; Schäfer, Petra K.; Trieb, Anke (Deutscher Verkehrs-Verlag, 2005)
Mit verschiedenen Bewirtschaftungsinstrumentarien und Strategien wird sowohl in Deutschland als auch in Japan versucht, den ruhenden Verkehr zu regulieren. Dabei gibt es eine Reihe von Aspekten, die im anderen Land bislang unbeachtet geblieben sind, so dass eventuell ein gegenseitiger Lernprozess stattfinden könnte. difu

Different nations have their own approach to dealing with the task of parking space management as part of their transport policy. By taking into account such aspects as the legal framework, use of public transport and local conditions, certain strategies are followed and variable methods are applied. Across Germany, stationary vehicles parked along public roads, assume an important role. For many years, parking space management has been in existence. In the case of Japan, this type of management has only belatedly been recognized as an effective way of exerting control over stationa´ry vehicles. This report covers aspects of parking space management in Japan by way of a comparison with Germany. In particular, the "garage law" that is specific to Japan is dealt with in detail. Some of the distinctive differences have not been much appreciated by either nation, which allows lessons to be drawn. difu
Keywords: Verkehr; Parkfläche; Parkplatz; Ruhender Verkehr; Wirtschaftlichkeit; Garagenverordnung; Straßenbelastung; Parkraumbewirtschaftung; Parkraummanagement; Internationaler Vergleich